Prevalence and Conditions Associated with Neuropathic Pain in Orthopaedic Patients of Bangkok Metropolitan Administration General Hospital - Yongyingsakthaworn, MD, Somkiat; Kulsiriitthikorn, BNS, Natcha (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: Neuropathic pain results from a primary lesion or dysfunction in the nervous system. Diagnosing neuropathic pain can be difficult, however, this condition is common in clinical practice. There is limited information on the prevalence of neuropathic pain in the Thai orthopaedic departments. The objective of this study was to investigate the prevalence of neuropathic pain and association factors in the orthopaedic out-patient clinic, Bangkok Metropolitan Administration (BMA) Hospital. Methods: A cross-sectional study of 400 patients attending the orthopaedic out-patient clinic, BMA hospital was conducted. The Thai DN4 questionnaire was used for the diagnosis of neuropathic pain. Main diagnosis and comorbidities were recorded. Descriptive statistics were used to provide the basic information. The Chi-square test was applied for the association and binary logistic regression was used for multivariate analysis. Results: The prevalence of neuropathic pain was 22.3%. The missed diagnosis rate was found to be 16.2%. There was statistically significant association between neuropathic pain and nerve entrapment.The most common symptoms used in practice by physicians for the diagnosis of neuropathic pain were reported as tingling (92.1%), pins and needles (78.7%) and numbness (70.8%) in this study. Conclusion: This study demonstrated a need to increase awareness of neuropathic pain in orthopaedic outpatient clinics. Health care providers should promote the DN4 questionnaire to diagnose neuropathic pain in clinical practice.